P42 ICG sentinel lymph node mapping in early cervical cancer (FRIENDS Study). (1st November 2019) - Stanciu, P; Ind, T; Kaur, M; Vroobel, K; Attygalle, A; Nobbenhuis, M
Abstract : Introduction/Background: The purpose of this study is to assess the detection rate of sentinel lymph nodes (SLNs) using Indocyanine Green (ICG) during robotic surgery for early stage cervical cancer. Methodology: This is a prospective, observational study that included women undergoing robotic surgery for early stage (FIGO ≤IB1) cervical cancer at Royal Marsden Hospital in London. From March 2015 until October 2018, 71 consecutive women were included and had SLN dissection using ICG. Thereafter, completion of surgery consisting of either trachelectomy, or radical hysterectomy was performed followed by pelvic lymphadenectomy if indicated according to hospital guidelines. No ultra-staging was applied. Results: A mean of four SLNs (SD 2.8) per patient were identified. SLNs were detected most frequently in common iliac, external iliac and obturator chains. Unilateral and bilateral SLN detection rates were 100% and 95.8%, respectively. Positive SLNs were detected in eight patients (11.3%). No additional positive nodes were found in the full lymphadenectomy samples. The sensitivity and negative predictive value of SLN dissection were both 100%. Conclusion: Florescent Robotic Indocyanine Endoscopic Node Detection Study (FRIENDS) has demonstrated that the use of ICG in robotic SLN dissection for early stage cervical cancer is feasible. In this setting, SLN dissection has the potential to replace a full lymphadenectomy and reduce morbidity. Replacement of ultra-staging with perioperative frozen section analysis of SLN to determine the extent of lymph node dissection might be justified. Disclosure: Nothing to disclose.